FEMINISME DI DUNIA MUSLIM: MENGUAK AKAR PERDEBATAN ANTARA PAHAM KONSERVATIF DAN REFORMIS - Sugeng Sugiyono (Thaqafiyyat : Jurnal Bahasa, Peradaban dan Informasi Islam, 2013)
This is a historical analysis of Muslim viewpoint, particularly on what hasoccurred in Egypt and Turkey, concerning the Reformists’ attempts to improve the status and role of women which have been socially and intellectually deprived for decades. It describes how Arab women, since the end of the nineteenth century, were beginning to struggle for greater freedom and wider opportunity to acquire knowledge in order that they would not lag behind the men. Such issues as freedom, veil (jilbâb) andwomen’s changing attitude have resulted in pros and cons. Thus, this article tries to reveal the core of the debate between the Conservatives and the Modernists related to the issue of women’s freedom which is still going on to date. The questions to answer include: a) the early outgrowth of feminism in the Arab world, b) the colonial role in shaping people’s opinion, c) the actors behind the Reformist movement, d) the roles of Muhammad Abduh, Qâsim Amîn, dan Hudâ Sya’rawî, and e) the Conservatives’ grounds to preserve its tradition and to reject any renewal.Keywords: feminism, conservative, reformist, tradition, reformation